2022
DOI: 10.1111/mice.12826
|View full text |Cite
|
Sign up to set email alerts
|

A novel U‐shaped encoder–decoder network with attention mechanism for detection and evaluation of road cracks at pixel level

Abstract: As the most common road distress, cracks have a substantial influence on the integrity of pavement structures. Accurate identification of crack existence and quantification of crack geometry are thus critical for the decision‐making of maintenance measures. This paper proposes a novel neural network for the detection and evaluation of road cracks at pixel level, which combines the advantage of encoding–decoding network and attention mechanism and can thus extract the crack pixels more accurately and efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…32 In crack detection, there have been attempts to combine the attention mechanism with available networks to improve detection efficiency. [33][34][35] For example, Pan et al 36 modified the backbone of DANet from ResNet101 to VGG19, namely SCHNet, and added a new attention mechanism named feature pyramid attention to improve crack detection accuracy. The results demonstrated that three attention mechanisms can increase MIoU by 10.88% than the baseline model.…”
Section: Introductionmentioning
confidence: 99%
“…32 In crack detection, there have been attempts to combine the attention mechanism with available networks to improve detection efficiency. [33][34][35] For example, Pan et al 36 modified the backbone of DANet from ResNet101 to VGG19, namely SCHNet, and added a new attention mechanism named feature pyramid attention to improve crack detection accuracy. The results demonstrated that three attention mechanisms can increase MIoU by 10.88% than the baseline model.…”
Section: Introductionmentioning
confidence: 99%
“…(2019) to accomplish pixel‐level detection of road cracks using black‐box images. In addition, many other deep learning solutions for pavement crack detection were also prompted with various successes in the last 5 years, including the DeepCrack (Zou et al., 2019), FPHBN (F. Yang et al., 2020), two‐step CNN (Liu et al., 2020), EDNet (Tang et al., 2021), U‐shaped encoder–decoder network (J. Chen & He, 2022), and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al, 2017), UNet (J. Chen & He, 2022), recurrent neural network (RNN; A. Zhang et al, 2018), and DeepLab (Meng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The current research on crack edge detection based on deep learning is mainly to improve the methods based on a fully convolutional network (FCN; Dung & Anh, 2019; Li et al., 2019; Ye et al., 2019), a self‐attention mechanism (Y. Pan et al., 2020; Song et al., 2019), CNN (Fei et al., 2019; S.‐Y. Kong et al., 2021; Ni et al., 2019; A. Zhang et al., 2017), UNet (J. Chen & He, 2022), recurrent neural network (RNN; A. Zhang et al., 2018), and DeepLab (Meng et al., 2020). Besides, some researchers utilize multi‐stage crack detection and achieve high‐precision crack edge detection by combining the classification algorithm with the segmentation algorithm (J. Liu et al., 2020; Meng et al., 2022).…”
Section: Introductionmentioning
confidence: 99%